2015
DOI: 10.1111/jog.12863
|View full text |Cite
|
Sign up to set email alerts
|

Rectal indomethacin use in pain relief during hysterosalpingography: A randomized placebo controlled trial

Abstract: Our study demonstrated a significant reduction in pain in patients who received a single rectal dose of indomethacin; therefore, we recommend the use of rectal indomethacin for reducing pain during a HSG procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Two studies were excluded: one because was related to the comparison of two different modes of lignocaine (spray and jelly) 13 and another one was not a randomized controlled trial. 14 Sixteen randomized controlled trials 3 , 6 , 15 - 18 , 22 , 23 , 28 were considered as primary relevant studies and included in this network meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies were excluded: one because was related to the comparison of two different modes of lignocaine (spray and jelly) 13 and another one was not a randomized controlled trial. 14 Sixteen randomized controlled trials 3 , 6 , 15 - 18 , 22 , 23 , 28 were considered as primary relevant studies and included in this network meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Of the sixteen randomized controlled trials analyzed, Cochrane Collaboration tool indicated that ten trials 15 - 19 , 22 , 24 - 27 used an adequate randomization and three trials 3 , 18 , 22 used an adequate allocation concealment. Five studies 3 , 17 , 18 , 22 , 24 reported adequate blinding and seven studies 3 , 16 , 19 , 23 , 24 , 26 , 27 were free of selective reporting. Ten trials 3 , 16 - 18 , 20 - 23 , 25 , 27 reported incomplete outcome data ( Table-II ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure is moderately invasive and exposes patients to ionizing radiation, and other (allergies) risks inherent to the use of iodinated contrast media. In addition, women may present with discomfort (pain) during and immediately after the procedure, and in rare cases, may lead to the dissemination of an underlying undiagnosed infection into the peritoneal cavity [10].…”
Section: Introductionmentioning
confidence: 99%